Analisis Investasi Teknologi Informasi terhadap Kinerja Keuangan Perusahaan Sektor Kesehatan - Channine Sabina Anwar; Saiful Saiful (Journal of Management and Bussines (JOMB), 2024)
This research aims to examine the effect of information technology investment on share value, Return On Assets (ROA) and Return On Equity (ROE) in health sector companies on the Indonesia Stock Exchange from 2019 to 2022. A research method based on the philosophy of positivism was used. to research a particular population or sample, data collection using research instruments, quantitative or statistical data analysis, with the aim of testing a predetermined hypothesis. The research results show that information technology investment influences the value of company shares, but has no effect on ROA and ROE. Limitations of this study include the focus on the health sector only and the low variability of the independent variables that can explain the dependent variable, indicating that other factors not investigated in the study also influenced the results by 73.4%. Conclusion, that the independent variables in this study have limitations in explaining the dependent variable. Keywords: Information Technology Investment, Company Financial Performance, Health Sector